Pablo Neruda's Song of Protest: History as Sensual Delight - Sicat, Ma. Teresa M. (Kasarinlan: Philippine Journal of Third World Studies; Vol 1 No 3 (1985), 2007)
Pablo Neruda’s “Song of Protest” faithfully reflects the realities of his time. It addresses the issues of imperialism and tyranny and celebrates the vision of the world created by their heroes and poets. It provides sensuous representations of the history of Latin America, characterized by oppression pervading in all areas of life, made manifest in specific events and concrete individuals. This paper examines the opus as a social product of a particular historical epoch. It discusses the life of Neruda, the governments and politics in Latin America, and how these provide an understanding of the forces that shaped both Neruda and his poetry. Ultimately, Neruda’s vision is of unity. That is, equality among men and justice for all. The contribution of Neruda’s poetry to the world is on how it inspires the poem-participator to become a dynamic participative historical force.
Keywords: protest poetry, Latin America, imperialism, equality, government, history